Vaginitis in women of reproductive age group: A hospital-based study from North India - Singh, Sweety; Saha, Rumpa; Suneja, Amita; Das, Shukla; Singh, N P (Eastern Journal of Medical Sciences, 2020)
Background: Vaginal discharge is a common problem faced by women of the reproductive age group seeking consultation in the gynecology outpatient department (GOPD). If not treated, it can lead to pelvic inflammatory disease, infertility and further complicate pregnancy. Objective: The present study explores the etiology and clinical presentations of vaginal discharge among women of reproductive age presenting to the GOPD of our tertiary care hospital. Materials and Methods: The study group comprised of 200 sexually active women of age group ?18 years attending our GOPD. Four vaginal swabs were taken from the posterior fornix under aseptic condition. Direct wet mount microscopy, gram stain, and culture on Sabaroud’s dextrose agar and Kupferberg media were carried out. Results: Prevalence of vulvovaginal candidiasis, bacterial vaginosis, trichomoniasis, and mixed infection was 30%, 20%, 2%, and 2%, respectively. Candida albicans were present in 55% patients and non-albicans Candida in 45%. The most common associated presenting symptom of patients presenting with the discharge was lower abdominal pain. Conclusion: Simple diagnostic techniques such as microscopy and culture help in diagnosis and the precise managementprocess of such women presenting with discharge and thus circumvent impending complication.